2014
DOI: 10.3897/natureconservation.7.5264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dichrostachys cinerea (l.) Wight & Arn (Fabaceae) on herbaceous species in a semi-arid rangeland in Zimbabwe

Abstract: Anthropogenic alteration of an environment and other disturbance regimes may enable the expansion of some native species into new geographical areas, a phenomenon observed with Dichrostachys cinerea. Five D. cinerea invaded sites, each approximately one hectare in size were assessed for the effects of D. cinerea on native herbaceous species diversity, richness, basal cover, litter cover, top hamper and plant vigour. The same attributes were studied in five uninvaded sites adjacent to, and equal in size to each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
2
13
2
Order By: Relevance
“…It is not only species richness and 1 6 1 5 7 2 1 4 8 1 1 3 1 2 4 9 1 0 3 1 1 6 5 3 1 2 0 2 1 2 9 2 7 2 3 2 2 1 7 1 9 1 8 2 4 2 5 2 6 2 8 3 2 3 composition that was negatively affected by sickle bush encroachment, but also the species diversity as encroached areas exhibited lower species diversity indices (both Shannon-Weiner diversity Index and Simpson's Index) than the non-encroached areas. This is in agreement with Mudzengi et al (2014) and Ayana (2007).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…It is not only species richness and 1 6 1 5 7 2 1 4 8 1 1 3 1 2 4 9 1 0 3 1 1 6 5 3 1 2 0 2 1 2 9 2 7 2 3 2 2 1 7 1 9 1 8 2 4 2 5 2 6 2 8 3 2 3 composition that was negatively affected by sickle bush encroachment, but also the species diversity as encroached areas exhibited lower species diversity indices (both Shannon-Weiner diversity Index and Simpson's Index) than the non-encroached areas. This is in agreement with Mudzengi et al (2014) and Ayana (2007).…”
Section: Discussionsupporting
confidence: 93%
“…This may indicate that D. cinerea encroachment was affecting the species richness and composition of the savannah plains of NSNP in particular and that of the rift valley system in general. Our result concurs with previous researches (Mudzengi et al, 2014) in reporting the negative effect of sicklebush encroachment on species richness and composition in the savannah ecosystems. Similarly, Sirami and Monadjem (2012) reported that there is significant decrease in species richness associated with shrub cover increase, which was also complemented in our study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations